SureCash: Promoting financial inclusion in Bangladesh - GHOSH, Aurobindo (Institutional Knowledge at Singapore Management University, 2018)
The case is set in December 2017, in Dhaka, Bangladesh, and describes the journey of a mobile financial service (MFS) provider called SureCash in Bangladesh, and the various facets of the MFS industry in the country. The MFS industry in Bangladesh is perceived to be oliogopolistic. While this is a difficult market for a new entrant to get into, it is not yet a saturated marketplace. This is primarily because a considerable part of the population in the country still remain ‘unbanked’. Amidst two significantly large players in the MFS market in Bangladesh, smaller players like SureCash have tried to create a niche by associating themselves with education fee collection initiatives, salary disbursement programs and government led projects like the Primary Education Stipend Progarm (PESP) launched by the Governent of Bangladesh. While associating with large scale projects like PESP has its own adavantages, taking up such large scale creation of MFS accounts has several challenges as well. The case on SureCash encapsulates this story by elaborating on the diffulcties faced by the company in digitising the PESP initiative and opening accounts for more than 10 million mothers. This had helped the company to promote Financial Inclusion in rural Bangladesh for a section of the demographic who were less likely to have acess to formal financial services than their male counterparts. Notably, Bangladesh is a country where a significant percentage of the total population still remined ‘unbanked’. What remained to be seen was wether SureCash could keep the mother’s engaged in their MFS platform over the long run? Also what could be the best strategy for SureCash to grow their presence in Bangladesh? The case and teaching notes elaborates the important elements of MFS in a developing economy and demonstrates how an MFS provider can help promote financial inclusion in rural economies. The case aso describes some of the unique characteristics of an oliogopoly market, and the risks associated with entering such a market. It also highlights some of the social and behavioural facets of Financial Inclusion related to MFS. The case can also be used to study the primary risks associated with an MFS market from the customer and agent perspective.